Fast and Versatile Pathway in Fabrication of Polyelectrolyte Multilayer Nanofiltration Membrane with Tunable Properties - Ahmad M. Alghamdi (Journal of Chemistry)
Thin film composite nanofiltration (NF) membranes are relatively new membranes compared to other types of pressure-driven membranes. However, they attract interest from researchers due to their versatility to be used in various applications. In this work, a new class of NF membrane was successfully fabricated through spin-assisted layer-by-layer assembly by depositing alternate layers of branched polyethylenimine (PEI) and poly(sodium 4-styrenesulfonate) (PSS) on ultrafiltration polysulfone (PSF) membrane. The suitability of the fabricated membranes for removal of divalent ions was investigated. It was found that the membrane consisting of (PEI/PSS)10–0.05 M NaCl showed MgCl2 rejection rate of 93.95% and permeation flux of 0.9 L/m2·h bar during tests performed using a crossflow permeation cell at a crossflow velocity of 0.65 m/s, MgCl2 feed concentration of 6530 ppm, pressure of 10 bar, temperature of 32.5°C, and pH of 6.5. This result suggests that this new fabrication method is suitable for producing polyelectrolyte multilayered (PEM) NF membranes that exhibit comparable membrane performance to commercial ones.